Is There a Chinese Model of a University? - Zha, Qiang; Shi, Jinghuan; Wang, Xiaoyang (International Higher Education, 2015)
This article presents an inquiry into the discourse of a possible Chinese model of the university. It sheds light on two major approaches to this discourse, and then discusses their merits and flaws. Finally, this article suggest situating this discourse in a broader context of globalization, which helps illuminates the notion that it is the combination of different characteristics (Confucian and Western) that makes the Chinese model unique.